Tyrosine Hydroxylase Expression in Differentiating Neurons of the Rat Arcuate Nucleus: Stimulatory Influence of Serotonin Afferents - Viktoria I. Melnikova; Michael V. Ugrumov; Evgenia V. Proshlyakova; André Calas; Jean Thibault (Neural Plasticity)
The influence of serotonin afferents on tyrosine hydroxylase expression in differentiating neurons of the rat arcuate nucleus was studied in vivo and in vitro. In the in vivo study, pchlorophenylalanine inhibited serotonin synthesis in fetal brain from the 11th to the 20th embryonic day. We then used semiquantitative immunocytochemistry to evaluate tyrosine hydroxylase levels in neurons of the arcuate nucleus in fetuses at the 21st embryonic day or in offspring at the 35th postnatal day. Serotonin depltion significantly decreased the tyrosine hydroxylase content in neurons of males and females at the 21st embryonic day and in males at the 35th